Health Cooperation in light of crises and sanctions in Developing Countries. (Case study in Syria) - Asaad, Bassel Anwar; Hasan, Riyam Ghandi; Kashmar, Mohammad Bassam (Magyar Gerontológia, 2024)
The methods, mechanisms, and plans for international health cooperation are still vague. However, many studies have confirmed that political affairs have great impacts on health bodies and organizations. Accordingly, the current study focuses on a special case which is the 13-year Syrian crisis, under the semi-collapse of the health system, foreign sanctions, and the unprecedented high demand for public health services. Hence, the problem can be expressed by the following question: Has health cooperation contributed to achieving social results during the Syrian crisis period under the increasing demand for health services? On the other hand, the study aimed to illustrate the reality of health cooperation (global, macro, micro) in the Syrian government areas, which suffer from external sanctions. Moreover, it aims to study, analyze, and predict the demand for health services in Syria (Latakia (using artificial intelligence models represented by the Facebook profit model and illustrating the social consequences of health cooperation in these areas. However, the descriptive analytical approach was used and artificial intelligence models were applied to analyze and predict data using Python. Accordingly, the study has an important set of results including: The economic sanctions imposed on the Syrian government during the current war have had a great impact on the economic situation in general, and the health sector in particular leading to a weak health system. Furthermore, the demand for health services in Latakia public hospitals increased significantly because of people displacement, in addition to high levels of poverty. Health cooperation in Syria has not resulted in effective social returns or to be able to encounter growing demand and minimize citizens’ burdens. Finally, artificial intelligence models are highly efficient and credible in predicting health demand, which contributes to the development of plans and strategies.